THE IMPLICATIONS AND IMPACT OF BREXIT - Čavoški, Aleksandra (Pravni zapisi, 2019)
Following the referendum held on 23 June 2016, the UK Government, in accordance with Article 50 TEU, notified the president of the European Council of its intention to leave the European Union. The decision of the UK to leave the EU known as “Brexit” has presented both the EU and the UK with complex challenges. While it is almost impossible to predict and assess all the effects of Brexit, the author will identify in this short overview the most important challenges facing both parties to the negotiations, as well as assess the wider implications of Brexit on future EU enlargement. The effects of Brexit in the UK are much deeper and long-lasting than in the EU. These include deepening political and social cleavages, economic effects and the need for comprehensive legal reform. Despite the initially gloomy prospects about the future of the European Union, the EU gradually reaffirmed its authority among member states and returned to ‘business as usual’. With regard to the wider impact of Brexit, these difficulties undoubtedly have already had a discouraging effect on any other member state who may have contemplated leaving the EU. Likewise, Brexit brought member states more closely together and exposed the importance and value of the EU project. This is particularly significant for the accession countries that over time have diminishing interest in EU membership due to the lengthy and demanding accession process. Key words: Brexit, impact, United Kingdom, European Union, enlargement, Western Balkans.